Comparison of Tryglicerides Levels and Total Cholesterol in Ischemic Stroke and Haemorrhagic Stroke Patients - Hasibuan, Hijriyah Putri Tarmizi; Thristy, Isra (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2020)
Background: Stroke is the second largest cause of death in the world. Stroke is classified based on its etiology as ischemic stroke and hemorrhagic stroke. Most large-scale studies on the risk of total cholesterol and triglyceride levels in stroke are not distinguished between ischemic and hemorrhagic strokes. Purposes: The purpose of this study was to determine the comparison of triglyceride and total cholesterol levels in ischemic stroke patients with hemorrhagic stroke. Method: Descriptive analytic study using medical records of patients at Medan Haji General Hospital in 2018-2019. The number of ischemic stroke patients is 28 patients and hemorrhagic stroke 28 patients with a total sample of 56 patients. Results: In ischemic stroke patients, the average value of triglyceride levels was 144.75 mg/dL and the average value of total cholesterol was 250.93 mg/dL. In hemorrhagic stroke patients, the average value of triglyceride levels is 126.93 mg/dL and the average total cholesterol level is 174.25 mg/dL. Conclusion: From this study we found a significant difference in total cholesterol between ischemic and hemorrhagic strokes. No significant difference was found in triglycerides between ischemic and hemorrhagic strokes.